2016
DOI: 10.1103/physreva.93.063861
|View full text |Cite
|
Sign up to set email alerts
|

Method for observing robust and tunable phonon blockade in a nanomechanical resonator coupled to a charge qubit

Abstract: Phonon blockade is a purely quantum phenomenon, analogous to Coulomb and photon blockades, in which a single phonon in an anharmonic mechanical resonator can impede the excitation of a second phonon. We propose an experimental method to realize phonon blockade in a driven harmonic nanomechanical resonator coupled to a qubit, where the coupling is proportional to the second-order nonlinear susceptibility χ (2) . This is in contrast to the standard realizations of phonon and photon blockade effects in Kerr-type … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
80
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 96 publications
(81 citation statements)
references
References 79 publications
1
80
0
Order By: Relevance
“…We note the multi-photon processes can also be induced in the hybrid superconducting system with only longitudinal coupling, which has been shown in our previous study [100]. In this work, we found that the secondorder nonlinearity can be about one order of magnitude stronger.…”
Section: Discussionsupporting
confidence: 80%
“…We note the multi-photon processes can also be induced in the hybrid superconducting system with only longitudinal coupling, which has been shown in our previous study [100]. In this work, we found that the secondorder nonlinearity can be about one order of magnitude stronger.…”
Section: Discussionsupporting
confidence: 80%
“…To this end, several recent proposals have studied possible nonlinearities in optomechanical setups exploiting, for example, an enhanced optomechanical nonlinearity based on an optomechanical system employing a few optical modes * hseok@kongju.ac.kr [25][26][27][28], an intrinsic mechanical nonlinearity [29,30], and the coupling of mechanical systems to a qubit [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…The entanglement potential, defined in Eq. (36), for the DSTS is given by the following simple formula [88]:…”
Section: Nonclassical and Classical Effects And Statesmentioning
confidence: 99%